Pengaruh Manajemen Ekstrakurikuler Terhadap Prestasi Non Akademik di SMA Budi Satrya - Nasution, Nabillah Ulfiyah; Fadhli, Muhammad (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2023)
This research aims to determine the influence of extracurricular management on non-academic achievement at SMA BUDI SATRYA. The dependent variable in this research is extracurricular management (X), the dependent variable is non-academic achievement (Y). The research population and sample is a sample of 32 teachers who will participate in this research, there are 14 male teachers and 18 female teachers. The teachers selected as respondents are those who have the capacity and are the main keys to the school. The data obtained were analyzed using the PLS analysis technique (Partial Least Square via SmartPLS Software. Based on the research results it can be concluded that: (1) Extracurricular Management has a positive and significant effect on Non-Academic Achievement at SMA BUDI SATRYA through partial testing, where scores were obtained The calculated t for Extracurricular Management is 5.203 ≥ t table, namely 1.654, so it can be concluded that Extracurricular Management has an effect on Non-Academic Achievement. Thus, hypothesis H1 in this study is accepted.